An experimental investigation on the mechanical performance of sustainable asphalt pavement incorporating waste glass powder - Hasan, Kamrul; Fariha, Noshin Anjum; Bashar, Jummana Benta; Alakhali, Ahmed K.; Fadzil, Mat Yahaya (IOP Publishing, 2025)
The disposal of waste glass (WG) poses a challenge due to its non-decomposable nature. Recycling WG plays a key role in sustainability, given its significant contribution to the global waste stream. This study investigates the use of waste glass powder (WGP), with a maximum size of 0.15 mm, as an aggregate inclusion at varying percentages (4%, 7%, and 10%) by weight to asphalt mixtures to enhance pavement strength and promote sustainable waste management. Therefore, in this research, mechanical characteristics, including Marshall stability and resilient modulus tests of modified asphalt mixtures, were evaluated. The results show that incorporating 7% glass powder yields the best Marshall stability and resilient modulus compared to the control mix. Although the 10% WGP modification resulted in the highest bulk density and voids filled with asphalt (VFA), it significantly reduced the resilient modulus. Thus, adding proper amount of glass powder significantly improves the hardness, strength, and resistance to structural deformation like rutting and cracking, making it a valuable option for pavement construction.